2018
DOI: 10.1039/c7sm02429k
|View full text |Cite
|
Sign up to set email alerts
|

Complex crystalline structures in a two-dimensional core-softened system

Abstract: A transition from a square to a hexagonal lattice is studied in a 2D system of particles interacting via a core-softened potential. Due to the presence of two length scales of repulsion, different local configurations with four, five, and six neighbors are possible, leading to the formation of complex crystals. The previously proposed interpolation method is generalized to calculate pair correlations in crystals whose unit cell consists of more than one particle. The high efficiency of the method is illustrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
66
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(72 citation statements)
references
References 98 publications
(113 reference statements)
5
66
0
1
Order By: Relevance
“…Here, k x and k y are the components of the wave vector k = {k x , k y , k z }; ρ(k x , k y ) is the Fourier-component of the local density fluctuations [35,36,37]; r x j and r y j are the radius-vector components of the jth particle. The angle brackets ... mean the ensemble averaging.…”
Section: Cluster Analysis and Structural Analysis Of Instantaneous Comentioning
confidence: 99%
“…Here, k x and k y are the components of the wave vector k = {k x , k y , k z }; ρ(k x , k y ) is the Fourier-component of the local density fluctuations [35,36,37]; r x j and r y j are the radius-vector components of the jth particle. The angle brackets ... mean the ensemble averaging.…”
Section: Cluster Analysis and Structural Analysis Of Instantaneous Comentioning
confidence: 99%
“…It was shown that this system forms three crystalline regions (low density triangular crystal, square crystal and high density triangular one). A dodecagonal quasicrystal phase appears in between of the square phase and the high density triangular one [27]. No stable ordered phase was identified in the region between the low density triangular phase and the square crystal.…”
Section: Introductionmentioning
confidence: 92%
“…The behavior of this system was studied in a number of papers in both 3D [3,[19][20][21][22] and 2D [23][24][25][26][27]. It was shown that at σ 1 = 1.35 the 3D system has complex phase diagram with several crystalline phases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The melting of systems with core-softened potentials was studied in Refs. [35][36][37][38][39][40] . It was shown that the system had a complex phase diagram with different crystal structures, including a dodecagonal quasicrystal.…”
Section: Introductionmentioning
confidence: 99%